Implantação e análise da ferramenta pfSense como firewall - Lopez, Paulo Alexandre Vieira Puga (2020)
Nowadays, a large amount of data is transmitted continuously via the Internet. Considering that a significant proportion of this data is sensitive, such as banking transactions, online shopping records of the customers, among others, exchange information, and safety can be a big risk. The crackers are at the ready with systems and advanced software, to carry out an attack, and to deliberately steal information and to infect the network, causing a large loss. In the face of the context of this work, will present the installation and configuration of the firewall is pfSense, a Softwarethe Free BSD (Berkeley Software Distribution) Open Source. Will be built with the hardware required for implementation, and some of the features of the tool, such as for access control, Access Control List (ACL), packet filtering, and network configuration Virtual Private Network (VPN) by connecting one of the branches of the array, in a manner up to the standards of safety, both physical and digital. The implementation of the firewall is outside the scope of this study it has as objective to keep the company data safe when you transmit it to the external environment in an efficient and robust. How to use this tool on an internal network, it is necessary to prevent the activities of the crackers. The study will be carried out through tests performed on a small-business business support market. You will be presented with the results of the implementation of a firewall in a production environment, which led to the improvement of the connectivity to the VPN, allowing you to add a few filters, increasing the availability of in-house infrastructure and prevent attacks and theft of information to meet the security needs of your organization.